Rancang Bangun Alat Sortir Jeruk Medan Berdasarkan Luas Lingkar Berbasis Mikrokontroler ATMega2560 - Ginting, Yafet Nikolas; Abdillah, Junindo; Sarimole, Frencis Matheos (FIKOM Universitas Bung Karno, 2023)
The increasing demand in the agricultural sector demands efficient fruit sorting solutions. This study considered the design and implementation of a orange fruit sorter combining ultrasonic sensor technology, servo motor, and infrared proximity. This tool aims to measure small to large dimensions of orange fruits. The use of infrared proximity aims to counter the fruit in each path where the orange runs to its container, and then the calculated information is displayed on the LCD screen to provide clear information for farmers. The main advantage of this tool is its ability to automatically classify orange fruits by size and amount. The integration of ultrasonic sensors and infrared proximity provides accuracy in distance measurement and fruit counting. This tool innovation provides unprecedented solutions and potential in orange fruit sorting, and can increase productivity in the agricultural industry. This research uses a technology design and implementation approach by integrating ultrasonic sensors, servo motors, IR proximity, on microcontrollers. The designed tool is able to classify orange fruits automatically by size and number. The design of this orange sorter promises to increase efficiency in the agricultural industry. The implementation of sensor technology and automation systems has the potential to provide the right solution for fruit sorting needs.